Adaptive Control System of the Arc Welding Equipment - Dambrauskas, A.; Karaliūnas, B.; Šulskis, D. (Elektronika ir Elektrotechnika, 2005)
There is presented investigation into defects of the arc welding flanges, they reasons and factors, which decide on quality of formation weld seams. If you like to optimize welding process, it is necessary to stabilize not only the speed of electric drives of the filler wire and little cart, but also the arc current, voltage, lengh and electrode wire melting speed. The formation principles of the adaptive control system there are presented, the function and structural schemes are obtained. Research results shows, that by employment of technical vision system and mathematical model of weld seams describing with logical operators the adaptive search system may be created. This system may quickly to change its parametres and structure, and in that way to optimize the same welding process. The problem on synthesis of the welding control system with the changeable structure and parameters was solved by using computer package Kvazio 1 with simplex search algorithms. The change laws of the amplification coefficients of the proportional and differential regulators where obtained. Modelling results shows, that the transitional process of the arc voltage is aperiodiocal and intimate to optimal. Because that is stabilizing the arc current, arc buring process and geometrical form of the weld seam. Ill. 6, bibl. 7 (in Lithuanian; summaries in Lithuanian, English and Russian).